CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).

High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.

High surface area porous carbon for ultracapacitor application by pyrolysis of polystyrene containing pendant carboxylic acid groups prepared via click chemistry - Chhatre, Shraddha; Aravindan, Vanchiappan; Puthusseri, Dhanya; Banerjee, Abhik; Madhavi, Srinivasan; Wadgaonkar, Prakash P.; Ogale, Satishchandra B. (Materials Today Communications, 2015)

Phenazine-containing poly(phenylenevinylene): a new polymer with impressive field emission properties - Chhatre, Shraddha; Ichake, Amol; Harpale, Kashmira; Patil, Sumati; Deshpande, Aparna; More, Mahendra; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2018)
Phenazine-containing poly(phenylenevinylene) (P(PHN-PV)) was synthesized using Wittig-Horner polycondensation of the appropriately designed monomers viz. 5,10-dioctyl-5,10-dihydrophenazine-2,7-dicarbaldehyde and tetraethyl ((2,5-bis((2-ethylhexyl) oxy)-1,4 phenylene) bis(methylene)) bis(phosphonate). The design embraces the specific motivation of incorporating the nitrogen-containing heterocycle viz. .phenazine in poly(phenylenevinylene) backbone. P(PHN-PV) exhibited reversible redox properties. In the field emission measurements performed on the film of P(F'HN-PV), the turn-on field was observed to be 1.93 V/mu m for the current density of 10 mu A/cm(2). The maximum current density of similar to 4.87 mA/cm(2) was achieved at the applied field of 3.84 V/mu m. The emission current showed impressive stability for 6 h at a constant current of 1 mu A (current density of about 20 mu A/cm(2)). These results emphasize the role of phenazine heterocycle with lone pair of electrons on nitrogen in lowering the oxidation onset and in turn reduction of the turn-on voltage.
Keywords: field emission; Phenazine; Poly(phenylenevinylene)

Biological macromolecule chitosan grafted co-polymeric composite: bio-adsorption probe on cationic dyes - Khairkar, Shyam R.; Pansare, V. Shubham; Shedge, Amol A.; Chhatre, Shraddha; Kulal, Dnyaneshwar K.; Patil, Vishwanath R.; Pansare, V. Amol (Polymer Bulletin, 2022)
Chitosan biological macromolecule is a versatile polymer; chemical modification has been carried out that lead to the formation of chitosan grafted polymers composites (Chito-g-PC). We proposed synthesis of six various Chito-g-PC as sorbents for toxic dyes. A novel graft copolymerization method based on radical polymerization with vinyl monomer like acrylic acid, acrylamide, N-isopropylacrylamide, methacrylic acid and polyacrylonitrile were utilized in order to address the large amount of swelling at four different pH buffers solution. The effect of initiator and monomer concentration, time and temperature on % grafting and % grafting efficiency were performed. Comparative characterization of Chito and Chito-g-PC were evaluated by SEM, XRD and FTIR, as well as solubility characteristics of the composites were determined by various pH buffer solution. Cationic toxic dyes Malachite green (MG) and Methylene blue (MB) were selected as the sorbet, and Chito-g-PC were used as biosorbents. Thermodynamic analysis showed that the sorption process was spontaneous and endothermic with an increased randomness. The sorption experiments were realized with six different Chito-g-PC for MG and MB at various pH.
Keywords: Acrylamide; acrylic acid; Bio sorbent; Chitosan biological macromolecule

X-ray fluorescence-based spray-on ``elemental barcodes'' - Pansare, Amol V.; Terrasi, Giovanni P.; Pansare, Shubham V.; Khairkar, Shyam; Shedge, Amol A.; Zote, Santosh W.; Chhatre, Shraddha; Barbezat, Michael; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials Technologies, 2025)
A novel spray-on elemental barcode technology is reported for the secure, permanent, and tamper-proof identification of polymeric and fiber-reinforced composite materials. This system utilizes the in situ reduction of metal salts to nanoparticles embedded within a polymer matrix, creating a unique barcode that is detectable through X-ray fluorescence (XRF). The barcode's composition is based on the metallic nanoparticle mixture and offers a semi-quantitative, non-destructive, and thermally stable method for material authentication. The process is straightforward, involving the manual application of metal salt solutions followed by mild heating, ensuring no significant alteration to the material's properties. The barcodes can be read through protective coatings or paints and are robust even under extreme conditions, such as high temperatures. This low-cost method does not introduce additional manufacturing steps and demonstrates significant potential for anti-counterfeiting and lifecycle tracking in various industries. Moreover, with an information density of up to 12 bits mm-1, this elemental barcode significantly surpasses the data storage capabilities of traditional optical barcodes. This approach holds promise for broad substrate applicability and can be expanded to other metals and reduction protocols, making it versatile for diverse material applications.
Keywords: authentication; barcoding; embedded nanoparticles; epoxy thermosets; fiber-reinforced composite; in situ reduction